The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1039/c7ee00682a
|View full text |Cite
|
Sign up to set email alerts
|

Multistage torrefaction and in situ catalytic upgrading to hydrocarbon biofuels: analysis of life cycle energy use and greenhouse gas emissions

Abstract: Well-to-wheel (WTW) life cycle assessment (LCA) of multistage torrefaction and in situ catalytic upgrading: overview of unit operations, modeling tools, and data sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 90 publications
0
40
0
Order By: Relevance
“…Saidi et al 6 addressed catalyst design matters, highlighting catalyst components and operating conditions favoring the production of higher value hydrocarbons from high oxygen content bio-oils, through hydrodeoxygenation (HDO). More recently, Zaimes et al 7 reported a life cycle assessment of energy consumption and greenhouse gas (GHG) emission of a multistage torrefaction and pyrolysis system to produce bio-oil for transport applications. Compared to single stage fast pyrolysis with HDO, for example, the proposed approach yields 80% reduction in GHG emissions and a significantly higher energy return on investment index.…”
Section: Introductionmentioning
confidence: 99%
“…Saidi et al 6 addressed catalyst design matters, highlighting catalyst components and operating conditions favoring the production of higher value hydrocarbons from high oxygen content bio-oils, through hydrodeoxygenation (HDO). More recently, Zaimes et al 7 reported a life cycle assessment of energy consumption and greenhouse gas (GHG) emission of a multistage torrefaction and pyrolysis system to produce bio-oil for transport applications. Compared to single stage fast pyrolysis with HDO, for example, the proposed approach yields 80% reduction in GHG emissions and a significantly higher energy return on investment index.…”
Section: Introductionmentioning
confidence: 99%
“…We use the minimum fuel selling price (MFSP) as an indicator of economic feasibility toward commercialization of the fuel pathway. On average, conventional diesel and gasoline are sold at $0.48 and $0.51 L −1 , respectively (U.S. Department Of F I G U R E 2 Survey of global warming potential (GWP) estimates of fuel pathways from alternative processes (Carrasco et al, 2017;Dutta et al, 2015Dutta et al, , 2016Heng et al, 2018;Hsu, 2012;Jones et al, 2009;Sorunmu et al, 2018Sorunmu et al, , 2017Zaimes et al, 2017;. Greenhouse gas emissions per 1 MJ of fuel used with GWP reduction shown in yellow (<50%), orange (50%-70%), green (71%-90%), and blue (>90%) bars.…”
Section: Discussionmentioning
confidence: 99%
“…Guaiacol is an electron rich, ortho-methoxy substituted phenol which is obtained from the depolymerization of lignin. [71] Catalytic fast pyrolysis of torrefied biomass, [72] followed by selective hydrodeoxygenation can produce guaiacol and phenol. [73,74] To expand the range of applications of guaiacol, Lopez and coworkers [65] used it in the alkylation of furfural-derived cyclopentanol (Scheme 4).…”
Section: Alkylation Of Phenolicsmentioning
confidence: 99%
“…Guaiacol is an electron rich, ortho‐methoxy substituted phenol which is obtained from the depolymerization of lignin [71] . Catalytic fast pyrolysis of torrefied biomass, [72] followed by selective hydrodeoxygenation can produce guaiacol and phenol [73,74] .…”
Section: Hydrodeoxygenated Products Of Fcfsmentioning
confidence: 99%